ACCOUNTABILITY AND BENEFITS OF VILLAGE FUND MANAGEMENT FOR COVID-19 HANDLING IN PEMALI DISTRICT BANGKA REGENCY - Karmawan Karmawan Karmawan; Sumar Sumar; Muhammad Qomaruddin Ridwan; Dony Yanuar (Fakultas Ekonomi, Universitas Bangka Belitung, 2022)
This study uses a qualitative methodological approach specifically examines the practice of managing Village Funds used for handling the COVID-19 pandemic. This paper examines the practice of managing Village Funds, especially in making changes to the Village Budget for activities to handle the COVID-19 pandemic and social safety nets in the village. This research is useful in providing an overview of the practice of managing Village Funds for handling the COVID-19 pandemic, especially at the beginning of the case and this research is also expected to provide views and insights on the factors that influence the accountability of village fund management. As well as as reference material for further research, especially in fields related to refocusing village fund management during the Covid-19 period. The research emphasizes the need for the Village Government in Pemali District to be able to provide understanding to the community regarding the use of Village Funds not intended as all Direct Cash Assistance (BLT). From the results of this study, it is hoped that it can provide benefits for various parties. This research is useful in providing an overview of the practice of managing Village Funds for handling the COVID-19 pandemic, especially at the beginning of the case and this research is also expected to provide views and insights about the factors that influence on village fund management accountability. As well as reference material for further research, especially in fields related to refocusing on village fund management during the Covid-19 period.